MeidyaCoM‐policy: Approach for modelling and checking repair policies for self‐healing systems - Mohamed Hadj Kacem; Imen Tounsi; Ahmed Hadj Kacem (IET Software)
Abstract The architecture of distributed systems is subject to certain failures: component failure, downed connections etc. These failures come from the dynamicity and complexity of these systems. As a solution to cure this weakness, adaptation plans can be added. However, the main difficulty of self‐adaptation emerges while considering the soundness of the adaptation and preservation of stylistic constraints of the system. The MeidyaCoM‐Policy, an architecture‐centric approach for modelling and checking repair policies to guarantee the success of the adaptation, is presented. This approach is a solution for applying self‐healing. A new unified modelling language (UML) profile that provides a visual notation for modelling repair policies is proposed to automatically transform UML models to Z notation using transformation rules coded in eXtensible styles language transformation (XSLT) language. These specifications are implemented under the Z/EVES theorem prover to prove specification soundness and consistency to guarantee the success of the adaptation. MeidyaCoM‐Policy applies to all architectural styles. It is instantiated for the publish/subscribe style and illustrated with a case study. An outline of the developed software environment is provided.